2011
DOI: 10.1083/jcb.201006114
|View full text |Cite
|
Sign up to set email alerts
|

Tinman/Nkx2-5 acts via miR-1 and upstream of Cdc42 to regulate heart function across species

Abstract: Cdc42 regulates cardiac function in mice and flies downstream of a conserved Tinman/Nkx2-5–miR-1 signaling network.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 72 publications
4
68
1
Order By: Relevance
“…It is possible that cdc42 gene expression is tightly regulated in Tin+ CBs in the developing DV. This idea is consistent with recent studies that showed that Cdc42 is an indirect target of Tin in the adult fly heart where it plays an important role in regulating heart function (Qian et al, 2011). Alternatively, Cdc42 activity may be preferentially up regulated in the Tin+ cells or down regulated in the Svp+.…”
Section: Discussionsupporting
confidence: 93%
“…It is possible that cdc42 gene expression is tightly regulated in Tin+ CBs in the developing DV. This idea is consistent with recent studies that showed that Cdc42 is an indirect target of Tin in the adult fly heart where it plays an important role in regulating heart function (Qian et al, 2011). Alternatively, Cdc42 activity may be preferentially up regulated in the Tin+ cells or down regulated in the Svp+.…”
Section: Discussionsupporting
confidence: 93%
“…The third cluster, miR-206/miR-133, is expressed primarily in somites during skeletal muscle development. The miR-1/miR-133a clusters are regulated by several important myogenic transcription factors, including SRF, MEF2C, and NKX2-5 (99). Deletion of miR-1-2 causes lethality between E15.5 and birth, as a result of ventricular septal defects (146).…”
Section: Micrornas In Cardiac Developmentmentioning
confidence: 99%
“…Sequence analysis of this upstream fragment revealed conserved consensus response elements corresponding to the early cardiac determination transcription factor Nkx2-5. Accordingly, the fly transcription factor Tinman and its homologue Nkx2-5 in mice have been shown to regulate the expression of miR-1 by directly binding upstream-specific cis -regulatory response elements (Qian et al ., 2011). The Rho-GTPase CDC42 interacts with Tinman/Nkx2-5 and cooperates to regulate miR-1 expression; more interestingly, CDC42 itself is a miR-1 target.…”
Section: Mirnas In Cardiac Development Function and Diseasementioning
confidence: 99%
“…The Rho-GTPase CDC42 interacts with Tinman/Nkx2-5 and cooperates to regulate miR-1 expression; more interestingly, CDC42 itself is a miR-1 target. This feedback regulatory network is involved in cardiac output and the formation of a normal myofibrillar architecture (Qian et al ., 2011). Similarly, SRF, Mef2c, MyoD, and Myogenin have been shown to directly bind consensus-conserved response elements in order to regulate miR-1 expression in cardiac and skeletal muscle tissues (Liu et al ., 2007; Rao et al ., 2006).…”
Section: Mirnas In Cardiac Development Function and Diseasementioning
confidence: 99%